„Tutaj przeszłość wrzeźbiła się w kamień” – o rytych i malowanych dekoracjach maswerkowych średniowiecznych budowli Torunia - Pilecka, Elżbieta; Kurkowski, Michał (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2013)
This article directly describes the problem of traceries and decorations that have been discovered recently on the elevations of medieval buildings in Toruń. These extensive researches have got not only a documentary value but also indicate the aims for conservatory work. Next, the examples from Toruń may also be the starting point for research workers on the rules of conversions in a certain type of architectural decorations in that historic period – from stone traceries and ceramic ones, in the artificial stone – to the engraved plaster and decorated in a polychrome style. Moreover, the analysis of the examples from Toruń has got a big methodological importance because this type of work on framings, blind – windows, peaks, buttresses and other architectonic details is the characteristic feature not only in the area of Ziemia Chełmińska but also at the whole shore of the Baltic Sea. It all points to the conclusion that the above problem is actually exemplified by its scale and the range of presented examples.